The Effect of Project-Based Learning (PjBL) Model on the Scientific Creativity at Grade VI Students of State Elementary School 091283 Marihat Huluan - Herbin Parningotan Siahaan; Asister Fernando Siagian; Sukardo Sitohang (International journal of technology and education research, 2026)
This study aims to improve the scientific creativity of sixth-grade students at Marihat Huluan Elementary School 091283 on the water cycle through the application of the Project-Based Learning (PjBL) model. This study used a pre-experimental method with a sample of 19 students. The research instrument was a scientific creativity test covering aspects of fluency, flexibility, originality, and elaboration. The results showed that the implementation of the PjBL model significantly improved students' scientific creativity. The average student score increased from 63.00, categorized as